Corneal elasticity after oxygen enriched high intensity corneal cross linking assessed using atomic force microscopy. (December 2016) - Diakonis, Vasilios F.; Likht, Nikita Y.; Yesilirmak, Nilufer; Delgado, Desiree; Karatapanis, Andreas E.; Yesilirmak, Yener; Fraker, Christopher; Yoo, Sonia H.; Ziebarth, Noël M.
Abstract: The purpose of this study was to assess anterior and mid corneal stromal elasticity after high intensity (HI) corneal cross linking (CXL), with and without oxygen (O2 ) enrichment, and compare these results to conventional CXL. Experiments were performed on 25 pairs of human cadaver eyes, divided into four different groups. Group 1 included corneas that did not receive treatment and served as controls; Group 2 included corneas that received conventional CXL treatment (Dresden Protocol: corneal epithelial debridement, 30 min of riboflavin pretreatment followed by 30 min of exposure to 3 mW/cm 2 of ultraviolet light); Group 3 included corneas that received HI CXL treatment (corneal epithelial debridement, 30 min of riboflavin pretreatment followed by 3 min of exposure to 30mW/cm 2 of ultraviolet light); and Group 4 included corneas that received the same treatment as Group 3, except that they were enriched with oxygen (4 L per minute pure O2 gas stream) during ultraviolet irradiation. In each group, corneas were subdivided to assess anterior stromal elasticity and mid stromal elasticity. Corneal stromal elasticity was quantified using Atomic Force Microscopy (AFM) through micro-indentation. Young's modulus for the anterior corneal stroma was 14.5 ± 6.0 kPa, 80.7 ± 44.6 kPa, 36.6 ± 10.5 kPa, and 30.6 ± 9.2 kPa, for groups 1, 2, 3 and 4 respectively. Young's modulus for the mid corneal stroma was 5.8 ± 2.0 kPa, 20.7 ± 4.3 kPa, 12.1 ± 4.9 kPa, and 11.7 ± 3.7 kPa, for groups 1, 2, 3 and 4, respectively. In the anterior stromal region, conventional CXL demonstrated a significantly different result from the control, whereas the two HI CXL protocols were not significantly different from the control. There were no statistical differences between the two HI CXL protocols, although only the HI CXL protocol with O2 enrichment was significantly different from the conventional CXL group. In the mid stromal region, once again only conventional CXL demonstrated a significantly different result from the control. There were no statistical differences between the two HI CXL protocols, and both HI CXL protocols were significantly different from the conventional CXL group. Oxygen enriched HI CXL seems to offer similar changes in corneal elasticity when compared to HI CXL without the presence O2 . Conventional CXL increases corneal stiffness more than HI CXL both with and without O2 enrichment. Highlights: Cornea stiffness was quantified after crosslinking with three different protocols. The traditional Dresden protocol was more effective than an accelerated protocol. Adding oxygen does not increase the stiffness in the accelerated protocol. Crosslinking increases mid-stroma stiffness, but to a lesser extent then anterior.